EVALUASI BUDAYA PENERAPAN K3 DENGAN KEPUASANPASIEN DALAM PENCEGAHAN COVID-19 DI PUSKESMAS BATU ANAM TAHUN 2022 - Rosmawaty Novera Munthe (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2022)
Safety is a form of practice that refers to our ability to eliminate or reduce the likelihood of a hazardous event occurring, which can interfere with our physical, mental and organizational functioning. Covid-19 is a new type of virus that has not previously been identified in humans. Covid-19 has started to become an epidemic in Indonesia since early March until now in August 2021. One of the efforts to reduce the possibility of a dangerous event, namely Covid-19, is to establish a safety culture. Culture will shape specific behaviors. This study aims to determine the Cultural Evaluation of the Implementation of K3 with Covid-19 Prevention Readiness at the Batu Anam 2022. The design of this study used an observational study with a cross-sectional approach where the population in this study were all patients who visited Batu Anam who met the requirements. The number of samples in this study was 96 people using consecutive sampling technique. Based on the results of the study, it was found that there was a relationship between safety values (p-value 0.003), leadership in safety (p-value 0.002), safety accountability (p-value 0.00), integrated safety (p-value 0.03), safety as a driving force (p-value 0.006) with patient satisfaction. Based on multivariate analysis, it was found that the most dominant variable related to patient satisfaction is the safety value with a p-value of 0.000 where the Exp (B) value is 12.068 where a good safety value 12 times will affect a person to feel satisfaction compared to a bad safety value. It is hoped that health workers will improve the application of safety values such as conducting morning briefings or coffee mornings, team sharing between the head of the public health and staff with the aim of strengthening team performance, building trust and also being useful for communicating about problems that exist in the public health.